Mulher Nagô : liderança feminina e as relações de gênero e parentesco no terreiro Santa Bárbara Virgem, em Laranjeiras - Torres, Díjna Andrade (2012)
Composed by approximately one hundred sons of Saint, the terreiro Santa Bárbara Virgem, located in the city of Laranjeiras, in the state of Sergipe, Brazil, was founded for over a century by africans brought from Benin, Nigeria and Togo, to work as slaves in the cultivation of sugar cane in this region. The two first leaders or Beg (designation for father of Saint) were men and since the death of Ti Herculano (last Beg of the Brotherhood), the terreiro has become led only by women, the Lôxas (designation for mother of Saint). From this perspective, it s important to draft the importance of women in a terreiro Nagô, that draws the attention for the accomplishment of a study that approach more deeply the role of women as a religious and family leader, and an analysis of the constitution of this leadership as a supporter of a secular tradition. The role of women and female leadership in the house is also linked to what the family of Saint members calls as purity. The Brotherhood Nagô calls itself the only pure of Brazil, because they keep the african heritage in the same way it was brought until nowadays. The objective of this study is to analyze the purity as na element that legitimizes the role of women as leaders of this community, as well as legitimizes the Brotherhood as the guardian of a tradition brought from their african ancestors, and to analyze gender and kinship relations that constitute and maintain the roles of female leadership of the Brotherhood. For this purpose, field research was conducted, open interviews with the Lôxa Bárbara Cristina dos Santos, the Mãe Pequena, Dona Ciza, the Patrão, José Maria de Jesus, and others members of the family of Saint members, in order to observe and analyze the ritualistic routine of the Brotherhood and how the hole of women and the utilization of the purity as one of the elements that legitimize the importance of women in this religion is set.